Relationship of Marriage Satisfaction and Religious Beliefs, Emotional Intelligence and Coping Strategies in Veterans and Physical Handicaps - A. Behnammoghadam; T. Hashemi; M. Birami; S. Yarian (Afarand Scholarly Publishing Institute, 2014)
Aims: Disability from any kind and in any form often leads to psychological crises through anxiety, fear, low self-esteem and psychological challenges. The aim of this study was to compare the physical veterans and disabled persons in the dimensions of marital satisfaction, emotional intelligence, religious beliefs, and coping strategies against stress. Methods: This causal-comparative correlational study was done on all male veterans (over 50%) and all male physical disabled (disabilities due to an accident) of Tabriz. 150 subjects from veterans by simple random sampling method and 150 subjects from physical disabled were selected using purposive sampling method and they were matched based on type and degree of disabilities and age. To collect data, Shereng Emotional Intelligence, Enrich Marriage Satisfaction, Folkman & Lazarous Coping Strategies and Serajzadeh Religious Measure questionnaires were used. SPSS 19 software was used to analyze the data using descriptive and inferential statistical tests. Findings: A significant difference was observed between marital satisfaction, emotional intelligence score, religious beliefs score, the problem-centered coping strategies and emotion-centered coping strategy score of the two groups. The correlation between the predictor variables (emotional intelligence, religious beliefs, problem-centered coping strategy and emotion-focused coping strategy) was 0.91 with marital satisfaction. These variables predicted 82% of marital satisfaction significantly (p<0.001). Conclusion: Veterans compared to physical disabled persons are more compatible with their disability and they are less impaired socially and mentally and they have more marital satisfaction as well.